Analisis Pengaruh Layanan Digital Perbankan Syariah terhadap Literasi Keuangan Syariah Generasi Milenial - Yasin, Rozaq Muhammad; Lailyah, Nurzahroh; Edris, Mochamad (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2021)
Good financial literacy, especially in the digital era now is important to be understood by millennials. The digitization of Islamic which is able to provide more efficient, safer, faster financial products and the risk of losing money is less well understood by this generation. Islamic digital banking services like mobile banking and internet banking, which describe the virtual process to support all services, are expected to be able to significantly increase the level of Islamic banking literacy and have a positive impact on business growth in general. This study used a quantitative descriptive research design. The sampling method used purposive sampling method. Data was obtained by using questionnaire which was distributed to 100 millennial respondents who used m-banking or i-banking in Kudus. The answers to the questionnaire were measured using a rating scale, then data was analysed by multiple linear regression. The results showed that m-banking and i-banking had a significant and positive effect to the literacy of millennials about Islamic banks in Kudus. It was proven by a significance value of 0.000 (p <0.05). The R-square value is 0.775, which means the contribution of the influence provided by m-banking and i-banking services to millennials Islamic financial literacy in Kudus is 77.5%, while the remaining 22.5% is influenced by other variables.